The arsonist : a mind on fire - Hooper, Chloe, 1973- (Seven Stories Press, 2020)
"The true story of the most devastating wildfire in Australian history and the search for the man who started it. What kind of person would deliberately start a firestorm? What kind of mind? On the scorching February day in 2009 that became known as Black Saturday, a man lit two fires in Victoria's Latrobe Valley, then sat on the roof of his house to watch the inferno. In the Valley, where the rates of crime were the highest in the state, more than thirty people were known to the police as firebugs. But the detectives soon found themselves on the trail of a man they didn't know. The Arsonist takes readers on the hunt for this man, and inside the strange puzzle of his mind. This book is also the story of fire in Australia, and of a community that owed its existence to that very element. The command of fire has defined and sustained us as a species--understanding its abuse will shape our future. A powerful true-crime thriller written with Hooper's trademark lyric detail and nuance, The Arsonist is a reminder that in an age of fire, all of us are gatekeepers"--